The Role of Serum Omega 3 Levels on Muscle Mass, Muscle Strength, and Physical Performance in the Elderly Community - Welly Salutondok; Nur Riviati; Yulianto kusnadi; Erial Bahar; Nova Kuniati; Syamsu Indra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
A B S T R A C TIntroduction. Old age is related to geriatric syndrome where there are several healthproblems that often occur related to a decrease in body function and an increase inthe inflammatory process. Decrease in muscle mass, muscle strength and physicalperformance will lead to a condition of sarcopenia and frailty syndrome in the elderly.The importance of prevention so that sarcopenia does not occur in the elderly byevaluating the factors that can cause it, one of which is controlling nutritional factors(macro and micro nutrients), such as in research, namely omega-3 macronutrients.The purpose of this study was to determine the correlation between serum omega-3levels with muscle mass, muscle strength, and physical performance in the elderlycommunity at Moehammad Hoesin Hospital Palembang. Methods. This research isan observational analytic study with a cross-sectional approach which wasconducted at the Integrated Geriatric Clinic Internal Medicine RSMH Palembangfrom November 2019 to November 2020. A sample of 21 people aged> 60 years wasexamined for muscle mass, muscle strength, physical performance and omega-levels. 3 serums. All data processing and analysis in this study used SPSS version25 for Windows. Results. Of the 21 subjects, it was found that women were 19people (90.5%) and 2 men (9.5%). The mean value of muscle mass was 37.65 ± 5.7,hand grip strength was 24.04 ± 5 kg, and walking speed was 6.72 ± 1.8 seconds per6 meters. There were 11 subjects with low serum omega-3 levels of 485.25 ± 110.19mg. There was a significant relationship between serum omega-3 levels and musclemass (p = 0.041) with moderate correlation strength (r = 0.448). Conclusion: Musclemass has a significant relationship with serum omega-3 levels in the elderly withmoderate strength. Meanwhile, muscle strength and physical performance did nothave a significant relationship.